2021
DOI: 10.1039/d1ta06742g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis design of a 3D interfacial structure for highly reversible lithium deposition

Abstract: Metallic lithium (Li) is a highly promising anode for high-energy-density batteries. However, irreversible Li deposition and Li dendrite growth during cycling, originated from unstable interface and chemistry disintegration, are the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Aiming to elucidate the unique twofold Li electrostripping and plating model of the 3D Li‐B‐C‐Al alloy anode at different current densities, a schematic illustration derived from the abovementioned results is depicted in Figure . Figure 5a shows that a porous LMS layer is generated after Li cycling, which consists of uneven Li electrodeposits and electrochemically inert “dead Li.” [ 42 ] Extended cycling of the Li anode results in the gradual and irreversible transformation of the original bulk Li to the accumulated LMSs, which is accompanied by an increase in inner cell resistance and concomitant cell degradation. In comparison, Figure 5b shows that Li electrodeposits are formed homogeneously within the 3D alloy anode and they grow in a bottom‐up behavior under low to medium current densities.…”
Section: Resultsmentioning
confidence: 99%
“…Aiming to elucidate the unique twofold Li electrostripping and plating model of the 3D Li‐B‐C‐Al alloy anode at different current densities, a schematic illustration derived from the abovementioned results is depicted in Figure . Figure 5a shows that a porous LMS layer is generated after Li cycling, which consists of uneven Li electrodeposits and electrochemically inert “dead Li.” [ 42 ] Extended cycling of the Li anode results in the gradual and irreversible transformation of the original bulk Li to the accumulated LMSs, which is accompanied by an increase in inner cell resistance and concomitant cell degradation. In comparison, Figure 5b shows that Li electrodeposits are formed homogeneously within the 3D alloy anode and they grow in a bottom‐up behavior under low to medium current densities.…”
Section: Resultsmentioning
confidence: 99%
“…76 Wang et al constructed a 3D graphene network host decorated with lithophilic inorganic components (Li 2 O and Li 2 CO 3 ) and coated with an insulating interphase of boron nitride. 77 Fang et al developed a 3D hybrid host consisting of Ag nanoparticle-embedded nitrogen-doped carbon macroporous fibers with the selective nucleation and targeted deposition of Li. 78 Shen et al prepared a house matrix composed of a carbon fiber matrix to release the volume change, facilitate uniform Li-ion diffusion, and serve as a physical barrier against electrolyte corrosion.…”
Section: Three-dimensional Collector Designmentioning
confidence: 99%
“…Pal et al reported an ether-aided ionic liquid electrolyte that offered superior Li metal deposition, high voltage (5 V) stability, and non-flammability. 77 Also, as mentioned above, researchers are now exploring the rational combination of various strategies for safer batteries. Yi et al prepared an ex situ artificial SEI film enriched with LiF and Li 3 N that was designed as a protective layer to suppress the growth of lithium dendrites.…”
Section: Other Approachesmentioning
confidence: 99%
“…[39,40] The conventional Cu, Ni-based, and carbon-based current collectors, nevertheless, suffer poor lithiophilicity with Li leading to high energy barrier for Li nucleation. [41] In this regard, decorating lithiophilic materials such as metals (i.e., Au, [42] Ag, [43] Zn, [44] and Mg [45] ) and metal oxides (i.e., ZnO, [39] Al 2 O 3 , [46] and MgO [47] ) among others, on 3D hosts is an effective strategy to improve the affinity between current collector and lithium. [48] However, such a design in general cannot guarantee the uniform Li deposition within the entire 3D structure, resulting from the preferential Li nucleation and growth on top of the porous skeleton.…”
Section: Introductionmentioning
confidence: 99%